KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP - Nova Dwi Tayala; La Ode Adili; Fahruddin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
The purpose of this study is to characterize the aptitude of SMP Negeri 2 Amonggedo, Konawe Regency, grade VIII students. When employing total sampling, up to 28 pupils from a single class are sampled. Since the instrument employed in this study is a written test to create exposition text, it is necessary to have an instrument to gather data on the capacity to write exposition text. The study's findings demonstrated that, out of the 28 students who made up the research sample, 4 students (14.28%) fell into the capable category and 24 individuals 85.72% of students are classified as incapable of creating exposition texts. In terms of the conclusion that can be drawn, pupils in grade VIII at SMP Negeri 2 Amonggedo, Konawe Regency, are traditionally classified as incapable of writing exposition texts. It is claimed that because individual pupils' capacity to meet the KKM of 68% (14.28%) has not yet attained the classical completeness standard of 85%. Judging from the level of students' ability from each aspect of assessment, namely content (100%), thesis (67.85%), series of arguments (78.58%), reaffirmation (75%), technical words (35.72%), argumentation relationship words (28.58%), mental verbs (0%), referring words (0%), persuasive words (14.28%). All aspects assessed are 8 aspects that fall into the category of incapable because classically the percentage does not reach the classical completeness criterion of 85%.